1997
DOI: 10.1074/jbc.272.16.10831
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage Factor II of Saccharomyces cerevisiaeContains Homologues to Subunits of the Mammalian Cleavage/ Polyadenylation Specificity Factor and Exhibits Sequence-specific, ATP-dependent Interaction with Precursor RNA

Abstract: Cleavage of pre-mRNA during 3 -end formation in yeast requires two protein factors, cleavage factor I (CF I) and cleavage factor (CF II). A 5300-fold purification of CF II indicates that four polypeptides of 150, 105, 100, and 90 kDa copurify with CF II activity. The 150-kDa protein is recognized by antibodies against Cft1, the yeast homologue of the 160-kDa subunit of the mammalian cleavage/polyadenylation specificity factor (CPSF). The 100-kDa subunit is identical to Brr5/Ysh1, a yeast protein with striking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 47 publications
3
82
1
Order By: Relevance
“…We also checked for the presence of the Clp1p subunit of CF IA in the eluates, but the low affinity of this antibody precluded the detection of this protein in the pellet fraction. However, given the tight association of the subunits of CF IA (17)(18)(19)(20)(21)(22)(23), Clp1p is likely to be recruited to the CTD as part of the CF IA complex. The interaction observed was resistant to treatment with RNase, arguing against the possibility of a RNA bridge (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also checked for the presence of the Clp1p subunit of CF IA in the eluates, but the low affinity of this antibody precluded the detection of this protein in the pellet fraction. However, given the tight association of the subunits of CF IA (17)(18)(19)(20)(21)(22)(23), Clp1p is likely to be recruited to the CTD as part of the CF IA complex. The interaction observed was resistant to treatment with RNase, arguing against the possibility of a RNA bridge (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…To date the interaction of cleavage͞polyadenylation factors with the CTD remains largely uncharacterized. In yeast 3Ј-end processing of pre-mRNA requires cleavage factor IA (CF IA), cleavage factor IB (CF IB), cleavage factor II (CF II), polyadenylation factor I (PFI), poly(A) polymerase, and the poly(A)-binding protein 1 (17)(18)(19)(20)(21)(22). CF IA, which is involved in both cleavage and polyadenylation, comprises four polypeptides: Rna15p, Rna14p, Pcf11p, and Clp1p.…”
mentioning
confidence: 99%
“…Yeast two-hybrid studies showed that the last 245 residues of CPSF-73 can interact with CPSF-100 [117]. Besides protein-protein interactions, Cft2p/Ydh1p can bind the pre-mRNA near the cleavage site [72,122].…”
Section: Cpsf-100 (Cft2p/ydh1p)mentioning
confidence: 99%
“…Interestingly, Yth1p does not appear to co-purify with the other CPSF subunits (Cft1p/Yhh1p, Cft2p/Ydh1p, Brr5p/ Ysh1p, Fip1p), even though they are in the larger CPF complex (Fig. 1B) [115,122]. CPSF-30 has a second isoform in humans (locus XP_945726), sharing 54% sequence identity.…”
Section: Cpsf-30 (Yth1p)mentioning
confidence: 99%
“…Further purification of these factors has led toward a determination of the number and identity of their constituent proteins. CF II contains the four peptides Cft1, Cft2, Brr5, and Pta1 (8). PF I contains the CF II subunits and the additional peptides Pfs1, Fip1, Pfs2, and Yth1 (9).…”
mentioning
confidence: 99%